Revolutionary nonviolence : organizing for freedom - Lawson, James M., 1928- (University of California Press, 2022)
A persuasive account of the philosophy and power of nonviolence organizing, and a resource for building and sustaining effective social movements. Despite the rich history of nonviolent philosophy, many people today are unfamiliar with the basic principles and practices of nonviolence--even as these concepts have guided so many direct-action movements to overturn forms of racial apartheid, military and police violence, and dictatorships around the world. Revolutionary Nonviolence is a crucial resource on the long history of nonviolent philosophy through the teachings of Rev. James M. Lawson Jr., one of the great practitioners of revolution through deliberate and sustained nonviolence. His ongoing work demonstrates how we can overcome violence and oppression through organized direct action, presenting a powerful roadmap for a new generation of activists. Rev. Lawson's work as a theologian, pastor, and social-change activist has inspired hope and liberation for more than sixty years. To hear and see him speak is to experience the power of the prophetic tradition in the African American and social gospel. In Revolutionary Nonviolence, Michael K. Honey and Kent Wong reflect on Rev. Lawson's talks and dialogues, from his speeches at the Nashville sit-in movement in 1960 to his lectures in the current UCLA curriculum. This volume provides a comprehensive introduction to Rev. Lawson's teachings on how to center nonviolence in successfully organizing for change.